Reducing the negative impact of accidents associated with the release of dangerous substances to environment - Iveta Marková; Jozef Kubás; Zuzana Štofková; Katarína Petrlová (Frontiers Media S.A., 2023)
BackgroundThe article is concerned with an evaluation of the current state of emergency readiness of industrial companies in the event of dangerous substance leakage and with a presentation of textile sorbents used for the purposes of capturing an escaped substance.MethodsA part of the article is concerned with the experimental designation of sorption capacity of hydrophobic, chemical, and universal sorption mats for chosen polar (water and alcohol) and non-polar (oil and gasoline) liquids. Experiments were realized according to Standard Test Method for Sorbent Performance of Adsorbents for use on Crude Oil and Related Spills, American Society for Testing and Materials (ASTM F726-17), type I. and Test methods for non-woven fabrics, European Union International Organization for Standardization (EN ISO 9073-6:2004). The aim of the article is an experimental designation of sorption capacity of textile sorption mats using two different methods, a comparison of the acquired results and a comparison of the acquired data with the data given by the manufacturer.ResultsTextile sorbents, which can, owing to their sorption ability, allow the elimination or mitigation of a negative impact of a possible accident in the company connected with an escape of a liquid dangerous substance were tested and compared with the established values. Based on the obtained results it is possible to state that sorption capacities of the chemical and universal mat for the substrate water are equal and consistent with the data given by the manufacturer. Textile sorption mats also have a comparable sorption capacity. The sorption capacity on the substrate gasoline is the same in all textile sorbents. The adsorption capacity per unit mass all type's sorbents was similar for non-polar liquids (gasoline was values from 6.41 to 6.57 and oil was values from 9.54 to 10.24).ConclusionThe acquired results confirmed the universality of textile sorption mats for gasoline. Sorption capacities of the chemical and universal mat for the substrate water are equal and match the data given by the manufacturer. Textile sorption mats have a maximum sorption output up to 60 s, afterwards the sorption capacity values remain unchanged.